"Put the phone away!": Does text message content influence perceptions of group member texting?. (February 2021) - Paskewitz, Emily A.; Beck, Stephenson J.
Abstract: Although mobile phone use in society and within organizations is commonplace, there are still questions about the appropriateness of phone use during meetings. On one hand, multicommunication researchers see mobile phones offering many benefits to employees including being constantly available and increasing meeting efficiency. On the other side, mobile phone use in meetings is seen as rude and a distraction from the task. This experiment focused on how knowledge of text message content may influence the positive or negative perceptions of mobile phone use in meetings. Four videos depicted an organizational meeting and different mobile phone message content (meeting-related, non-meeting related, no knowledge of the message, no mobile phone use). After watching the video, participants evaluated the texter and overall meeting. Results from a student ( N = 415) and a professional sample ( N = 410) showed that an absence of mobile phone use was best for individual and meeting level outcomes. Meeting-related text messages were generally viewed more positively than non-meeting related messages or not knowing the message. Differences were also found between the two samples for individual and meeting level outcomes. These findings are discussed in light of meeting norms around mobile phone use, along with implications for meetings. Highlights: Mobile phones are popular in meetings for efficiency but can be a distraction. Human beings have norms for appropriate mobile phone use. Students and professionals have similar norms for mobile phone use in meetings. Videos with different text message content influenced perceptions of texters. Avoiding mobile phone use during meetings is preferred.